Inspection of Foundation Structures with Pile Integrity Test (PIT) of Steel Tower Building - Citra, Zel; Malinda, Yosie; Dwiyanto Wibowo, Paksi; Ferial Ashadi, Reza; Wibisono, Anom; Apdeni, Risma (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Pile Integrity Test (PIT) is a tool from Pile Dynamic Inc. (PDI), consisting of a mini-computer, accelerometer, and hammer. Integrity testing on piles using PIT equipment is carried out by analyzing one-dimensional wave propagation provided by hammer blows on the pile head. An accelerometer sensor installed on the pole will read the reflection that occurs during wave propagation on the pole head. The wave propagation speed that occurs in concrete will range from 3,500 m/s to 4,200 m/s. The PIT test results indicate the reduction in impedance in the pole by the BTA value, which compares the theoretical impedance value to the residual impedance. From the results of the Pile Integrity Test carried out at three pile points, it was found that all samples experienced a reduction in impedance around a depth of ± 3.0 meters below the sensor with BTA values of 75%, 78%, and 72% and fell into the damaged category. The reduction in impedance at a depth of 3 meters is most likely part of the connection between piles because one pile point uses 2–3 spun piles, with the length of 1 spun pile being 9 meters. From the results of visual observations, it can be seen that the condition of the existing spun pile and pile cap is still quite good.